The Problems of Early Childhood Education During COVID-19: An Appraisal Analysis of “Does Early Childhood Education Still Matter during Covid-19? On The Jakarta Post - Ma’mun, Nadiah; Riyono, Ahdi (Institut Agama Islam Negeri Ponorogo, 2021)
This article explores the rhetoric of Yuliana in describing the difficulties of parents, teachers, and school administration during covid-19 health crisis. This study is guided by content analysis and the analytical framework of Appraisal from systemic functional linguistics, which concerned with the language of evaluation. The study reveals that in order to show the problematic matters of poor early students, their parents, the teachers, and the owner of a daycare center, Yuliana utilizes the appraisal system in a variety ways, with the aim to show some alternative solutions to the owners of the schools and the governments as to invest more because of the importance of early education for young generations for the future.